Band Structure–Controlled Zn1−xCdxS Solid Solution for Photocatalytic Hydrogen Production Improvement via Appropriately Enhancing Oxidation Capacity. Issue 3 (15th January 2021) - Huang, Meiling; Luo, Xingyun; Ai, Zizheng; Li, Yanlu; Zhang, Kang; Shao, Yongliang; Huang, Baibiao; Wu, Yongzhong; Hao, Xiaopeng
Abstract : The solid solution semiconductor Zn1− x Cd x S is suitable for the study of improving hydrogen production on the basis of energy band engineering. Herein, the most suitable bandgap and conduction/valence band position for hydrogen production are confirmed by balancing the relationship between light absorption capacity and redox reaction. Furthermore, it is verified that hydrogen production activity could also be greatly enhanced by improving the oxidation capacity while keeping the reduction capacity based on the principle of mutual promotion of the two half‐reactions in the water‐splitting process. First‐principles calculations are performed using density functional theory (DFT) methods to confirm the band structure composition of Zn1− x Cd x S. The optimal hydrogen production activity is 15.58 mmol h −1  g −1 . It provides a new idea for the solution of oxygen production and even overall water splitting with photocatalysis, although herein only the best conditions for hydrogen production are explored. Abstract : The most suitable bandgap and band edge of Zn1− x Cd x S for hydrogen production are confirmed by balancing the relationship between light absorption capacity and redox reaction. Furthermore, hydrogen production activity can be greatly enhanced by improving the oxidation capacity while keeping the reduction capacity based on the principle of mutual promotion of the two half‐reactions in the water‐splitting process.